Algorithm of the breast cancer complex treatment consider dynamics of the primary tumor immunophenotype - O. B. Druzhkov; M. O. Druzhkov; I. G. Gataullin (Опухоли женской репродуктивной системы, 2014)
The study was undertaken to elaborate combination treatment tactics for local recurrences with regard to a change in the immunophenotypes of a primary tumor and locally advanced recurrence of breast cancer (BC). The change of the immunophenotype of BC from primary tumor to local recurrence was studied. A treatment algorithm for local recurrent BC was developed in accordance with the above changes and the clinical form of a recurrent tumor.